Magnetic and transport properties driven by lattice strain in La₀.₇Ca₀.₃MnO₃/BaTiO₃ and La₀.₇Sr₀.₃MnO₃/BaTiO₃ bilayered films - Prokhorov, V.G.; Komashko, V.A.; Kaminsky, G.G.; Yu, K.K.; Jun, S.J.; Park, S.Y.; Park, J.S.; Lee, Y.P.; Svetchnikov, V.L. (Физика низких температур, 2007)
The microstructure and the magnetic and transport properties of La₀.₇Ca₀.₃MnO₃ and
La₀.₇Sr₀.₃MnO₃ films deposited on a BaTiO₃ layer (LCMO/BTO and LSMO/BTO) and on a
LaAlO₃ (001) single crystal (LCMO/LAO and LSMO/LAO) by rf-magnetron sputtering using
«soft» (or powder) targets are investigated. The films grown on BTO demonstrate biaxial tensile
in-plane and compressive out-of-plane strains, while the films grown on LAO, in contrast, manifest
compressive in-plane and tensile out-of-plane strains. The films with biaxial tensile in-plane
lattice strain undergo the magnetic transition at a higher temperature than that for the biaxial
compressive case. This argues that the Mn–O–Mn bond-angle variation, controlled by the lattice
strain, plays a more important role in the formation of the spin ordering than the attendant modification
of the Mn–O bond length. It was shown that the magnetic inhomogeneity, expressed by a
significant difference between the field-cooled and zero-field-cooled temperature-dependent magnetization,
has a metallurgical rather than an electronic nature, and is controlled by the crystal
lattice distortion and the microstructure defects. The observed enhancement of the magnetoresistance
effect in the LSMO/BTO bilayer at room temperature make this object greatly beneficial
in the development of new hybrid ferromagnetic/ferroelectric devices.